Nanoparticles enhanced phase change materials (NePCMs)-A recent review - Tariq, Syeda Laraib; Ali, Hafiz Muhammad; Akram, Muhammad Ammar; Janjua, Muhammad Mansoor; Ahmadlouydarab, Majid (Applied thermal engineering, 2020)
•Addition of nanoparticles, with specific volume concentration, enhanced the thermal conductivity of base PCM.•Application of NePCMs in buildings reduced the energy consumption.•Use of NePCMs enhanced the thermal management of modern electronics.•The use of NePCMs in smart textiles improved the thermal stability and durability. Phase change materials (PCMs) play a prime role in the development of sustainable energy and engineering systems for viable future, with their remarkable phase change properties. The heat energy absorbed and released by PCMs, over a specific temperature range, has become a prominent contender in many engineering applications that encompass thermal, solar, electronic, battery thermal management, textiles, heat pipes and food packaging. Apart from having high latent heat storage capacity, PCMs possess low thermal conductivity, which requires nanoparticles to be incorporated. Effectiveness of thermal conductivity of PCM can be increased by adding nanoparticles and resulting material is known as Nanoparticle-enhanced PCM (NePCM). This paper presents the comprehensive review on the preparation techniques as well as the applications of NePCMs in various fields. It is expected that this review will intend readers to provide some insight to explore the further applications and essential properties of NePCMs.